Pengaruh EPS, DER, dan ROA pada Harga Saham Perusahaan Teknologi Indonesia Periode 2020–2024 - Hafidz Insanu Izza Al-Maris; Maretha Ika Prajawati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study examines how Earnings per Share (EPS), Debt to Equity Ratio (DER), and Return on Assets (ROA) affect the stock prices of technology companies listed on the Indonesia Stock Exchange over the 2020–2024 period. The research employs a quantitative methodology utilizing panel data regression analysis. Samples were determined through a purposive sampling approach, limited to firms that consistently published comprehensive annual reports throughout the observation years, resulting in a total of 12 companies. The findings reveal that ROA has a significant positive relationship with stock prices, whereas EPS and DER do not demonstrate any statistical significance. Collectively, these three variables have a meaningful effect on stock price fluctuations, reflected in an Adjusted R² value of 0.2789. The outcomes imply that within Indonesia’s technology sector, investors perceive the efficiency of asset management as a more credible signal than traditional indicators such as EPS and DER. This research contributes to the existing body of knowledge by emphasizing industry-specific factors influencing stock price formation and provides valuable recommendations for investors and regulators in assessing the financial performance of technology firms.